Intentional Head Injury: Survivor Victim’s Profile, Gender Differences and Role of Alcohol Use at Manipal Teaching Hospital, Pokhara, Nepal - Atreya, Alok; Kanchan, T; Karmacharya, BG (Birat Journal of Health Sciences, 2017)
Introduction Head is a vulnerable area in human body and also a favorable site for assaults which is easily accessible by assailant’s raised arms. Objective The objective of this study was to evaluate the socio demographic spectrum, severity, radiological findings and outcome of victims assaulted to the head. Furthermore, the study aims to correlate such findings to the role of alcohol use in Nepalese context. Methodology This longitudinal prospective study includes victims of traumatic head injury as a result of physical assault who were admitted in the Neurosurgery Unit of Manipal Teaching Hospital Pokhara, Nepal from 1st January to 31st December 2015. Results Intentional head injury accounted to 17.40% of all head injury cases admitted during the study period. Among them 48 (76.19%) were males and 15 (23.81%) were females. The minimum age of the patient was 15 years and maximum was 84 years with a mean age of 33.89±14.67 years. Most of the victims of physical assault belonged to the age group of 21 to 30 years. Blunt object was the most commonly used for assault. Loss of consciousness was associated only with 49.21% of cases and 14.29% cases had bleeding from ear and/or nose. More than 75% of the cases had significant radiological finding in the form of fracture and/or intracranial lesion. Majority of the victims during the study were treated conservatively and were discharged with advice. Alcohol use was involved in 36.51% cases of intentional head injuries. Conclusion Intentional injuries under the influence of alcohol use are totally preventable public health concerns. It can be ascertained that reducing availability and improving the environment in which alcohol is sold and consumed can result in a dramatic reduction in violent crimes. Birat Journal of Health Sciences Vol.2/No.1/Issue 2/ Jan - April 2017, Page: 102-105